The effect of government cuts of doctoral scholarships on science - Giulia Rossello (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
I provide estimates of the impact of government cuts on PhD scholarships in Science. I leverage a unique quasi-natural experiment, the staggered cuts made by the Hungarian Government between 2010 and 2021 to expand Orban's political influence over the university system. The political aim of the cut ensures that it is exogenous to the economic cycle and to the scientific activity of universities. My analysis couples the complete enrolment records of doctoral students in the country around the years of scholarship cuts with a generalized difference-in-differences approach. I find that while government cuts of PhD scholarships have an ambiguous effect on students' attainments, the policy has a clear negative effect on Science. That is, the severe reduction of scholarships increases the chance of completing the PhD by 1 pp, and the effect is stronger for female students. However, this positive effect is counterbalanced by a reduction of a similar amount of entry rates for females and non-traditional students. This suggests that besides training might improve, or the system might become more efficient, this is at the expense of social inclusion. Additionally, the effects of cuts on scientific production are negative both in terms of quantity and quality. The productivity of doctoral students drops by 2 pp while their scientific quality decreases between 0.2 pp and 1 pp. My results suggest that the reduction of doctoral scholarships might produce efficiency in terms of student attainment but at the expense of social inclusion, scientific production, and quality.
Keywords: H75; I23; I24; I25; 330; Government Appropriation; Higher Education; Doctoral Scholarships; Event Study; Difference in Differences